Осмислення зв'язку «людина - соціум» у сучасній традиціоналістській прозі: відчуження, самотність, «social exclusion» - Ставнича, О. (Літературознавчі обрії. Праці молодих учених, 2010)
Specificity of an artistic interpretation of the relationship «human-society» is investigated through the categories of «estrangement» and «solitude», which are used in existentialist philosophy, and the conception of «social exclusion» which belongs to the social psychology field. Such modes of social estrangement revelation as self-estrangement, solitude, deviant behavior, «social exclusion» are contemplated in compositions by V. Shevchuk, Yu. Mushketik, M. Lazarchuk, G. Tarasuk and some other writers. The use of interdisciplinary elements allows the author of the article to characterize the conceptual and meaning aspect of the communication between an individual and society showed by the writers.